Sportsmen mnestic functions’ features in conditions of contest and postcontest functioning - Гант, О. Є.; Сушкова, М. В. (Slobozhanskyi Herald of Science and Sport, 2011)
We characterize the features of verbal memory in terms of competitive athletes and post-competition activity.